The Rise of the East and the Far East: German Labor Markets and Trade Integration - Jens Suedekum; Sebastian Findeisen; Wolfgang Dauth (European Regional Science Association (ERSA), 2012)
The unprecedented economic rise of Eastern Europe and China in the last two decades has triggered concerns in developed Western market economies about adverse effects for domestic labor markets trough increased import competition. Simultaneously, exports from developed countries to these new destination markets have also surged. We analyze the effect of this enormous rise in trade integration on German labor markets between 1988 and 2008, using detailed administrative data. We exploit the variation in initial industry variation across German regions, before the onset of these trade shocks, and instrument for regional import and export exposure using trade flows from other highly-developed countries with East Europe and China. We find large effects of export and import exposure to East Europe; on average exports are estimated to have increased manufacturing employment by 3.99 percentage points, whereas imports increased manufacturing employment by 2.33 percentage points. We find no effects of trade integration with China on the employment margin. We complement our findings with results on regional wage growth, inequality, industry churning and population shifts. Using data at the worker level, we show that workers specialized in export (import) industries before the onset of trade shocks, have a higher (lower) probability of subsequently being employed and have more (less) stable employment outcomes, defined as working in the same firm or industry. These effects of trade on worker outcomes are larger and more robustly estimated for Eastern Europe.
Keywords: 330